The Influence of Tiktok Media’s Popular Language on Students Communication Styles - Akbar, Azriyansyah Fadil; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2024)
TikTok media has become an important part of everyday life because TikTok is a popular social media platform, TikTok has developed into a global phenomenon with millions of users. This study aims to explore the influence of popular language on TikTok social media on the communication styles of students at Universitas Muhammadiyah Sidoarjo (UMSIDA), using the diffusion of innovations theoretical framework. The influence of popular language in TikTok media on the communication style of Communication Science students of Universitas Muhammadiyah Sidoarjo class of 2021 is the subject of this study. This study uses quantitative methods. The hypothesis was tested with Simple Linear Regression Test. The results of the study show that the popular language of TikTok media has an effect on the communication style of the 2021 class of Communication Science students at Muhammadiyah Sidoarjo University, with a significance level of 0.000 <0.05. The results of this study indicate that the effect of using the popular language of Tiktok media on the Communication Style of Communication Science students of Muhammadiyah Sidoarjo University class of 2021 is very significant with a coefficient of determination or R square value of 64,6%. While the remaining 35,4% is influenced by other factors.